Pengenalan Aplikasi Power Point Kepada Anak-Anak di DK. Sumberrejo 1 - Diana Wahyuni Firnanda; Muhammad Zuhri Ardiansyah; Muhammad Ishom Sholid Murtadho; Andi Atilla Bachri; Alysia Dewi Nur Masyithoh; Nonot Wisnu Karyanto (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
As technology continues to develop, the use of software applications such as Microsoft Power Point is becoming increasingly important in the learning process, including for children at DK. Sumberrejo 1. Power Point has great potential for learning or training and is an even more interesting way of delivering material. Microsoft Power Point is an effective tool in helping convey material visually and interactively, which can improve children's understanding. The problem that children often face is difficulty in distinguishing icons and understanding the functions of the Power Point application. This can hinder children's ability to make maximum use of this Power Point application in daily learning. The introduction of Microsoft Power Point aims to create a learning process in the future. By understanding the basics of using Power Point you can create more interesting presentations thereby increasing motivation and enthusiasm for learning. With this introduction, it is hoped that the children being taught will be able to know and apply the basic knowledge that has been taught. The method for introducing Power Point is the reflection method, where the material is given orally and also transmits how to apply it. The steps in using Microsoft Power Point are explained in detail to ensure children can understand and apply knowledge effectively so that Power Point can be an adequate learning medium for now.